Developing technologies in food science : status, applications, and challenges - Meghwal, Murlidhar; Goyal, Megh Raj (Apple Academic Press, 2017)
"This new volume, the 7th in the Innovations in Agricultural & Biological Engineering book series, focuses on emerging trends, applications and challenges in food science and technology. While food science and technology is not a new field, it is constantly changing due to new technology, new science, and new demands. This multidisciplinary book not only considers food processing, preservation, and distribution, but it also taken into account the consumer's wants and needs. Included is a report of the status of agricultural production and food processing industries in India with a national and international perspective. The book then goes on to explore new and emerging trends in the science and technology in the field, including" applications of nuclear magnetic resonance in food processing and packaging management" ultrasound processing" application of biocomposite polymers in food packaging" bioprocessing and biorefinery approaches for sustainable fisheries" adding value to food from food waste through biotechnological intervention" functional foods and the fortification of foodsCovering a broad selection of topics in the field, the volume will be of interest to food scientists and technologists, food process engineers, researchers, faculty and students, and many others the food science and technology industry."- Resumé vydavatel
Keywords: potravinářský průmysl; biotechnologie; inovace; food industry; biotechnology; innovations; sborníky; elektronické knihy; papers of several authors; electronic books